G Company's war : two personal accounts of the campaigns in Europe, 1944-1945 - Egger, Bruce E., 1923- (Book collections on Project MUSE., 1992)
This unique account of combat in World War II provides parallel day-to-day records of the same events as seen by two men in the same company, one an enlisted man, one an officer. G Company's War is the story of a World War II rifle company in Patton's Third Army as detailed in the journals of S/Sgt. Bruce Egger and Lt. Lee M. Otts, both of G Company, 328th Regiment, 26th infantry Division. Bruce Egger arrived in France in October 1944, and Lee Otts arrived in November. Both fought for G Company through the remainder of the war. Otts was wounded seriou.